2015
DOI: 10.1016/j.jacep.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Contact Force in Atrial Radiofrequency Ablation

Abstract: Although high CF (>20 g) resulted in more acute tissue edema than low CF (<10 g), chronically there was no difference in lesion size, quality, or transmurality. Appropriate CF targets for atrial ablation may be lower than previously thought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…In addition, contact force maps during ablation were created by analysis of ablation tags. Gap sizes determined on these ablation contact force maps using a lower contact force threshold of 5g (11) were also compared to eventual chronic macroscopic gap sizes.…”
Section: Ablation Gap Sizementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, contact force maps during ablation were created by analysis of ablation tags. Gap sizes determined on these ablation contact force maps using a lower contact force threshold of 5g (11) were also compared to eventual chronic macroscopic gap sizes.…”
Section: Ablation Gap Sizementioning
confidence: 99%
“…Before commencing ablation, smooth catheter movement along the proposed line was confirmed. Ablation was performed via the ablation catheter (3.5mm irrigated tip at 17mls/min) at a temperature of 42°C and a power of 30W with sufficient contact force to maintain catheter stability (11). Ablation was performed as a continuous drag with the catheter moved every 30 seconds.…”
Section: Electroanatomic Mapping and Ablationmentioning
confidence: 99%
“…Despite best efforts, arrhythmia recurrence following catheter ablation is commonly observed . Prior studies have shown that there can be a significant edema formation during ablation and some of the recurrences has been attributed to the creation of this edema and as a result, reversible block . Deeper and bigger lesions can be made by using higher contact force, but higher contact force is also associated with more complications like steam pops as well as edema .…”
Section: Introductionmentioning
confidence: 99%
“…In animal models, it has long been established that ventricular and atrial lesions can be visualised immediately following ablation. 47,55 Detailed delineation of the pharmacokinetics of gadolinium within acute RF injury lesions 24 has been performed, and has been correlated with nonenhanced sequences such as T2-weighted, turbo-spin echo techniques. Non-contrast agent-based imaging techniques are particularly attractive as they can be repeated multiple times.…”
Section: Acute Lesion Imaging (<4 Hours)mentioning
confidence: 99%